Mental Health Recovery Narratives and Their Impact on Recipients: Systematic Review and Narrative Synthesis. (October 2019) - Rennick-Egglestone, Stefan; Morgan, Kate; Llewellyn-Beardsley, Joy; Ramsay, Amy; McGranahan, Rose; Gillard, Steve; Hui, Ada; Ng, Fiona; Schneider, Justine; Booth, Susie; Pinfold, Vanessa; Davidson, Larry; et al.
Objective: Mental health recovery narratives are often shared in peer support work and antistigma campaigns. Internet technology provides access to an almost unlimited number of narratives, and yet little is known about how they affect recipients. The aim of this study was to develop a conceptual framework characterizing the impact of recovery narratives on recipients. Method: A systematic review of evidence about the impact of mental health recovery narratives was conducted. Searches used electronic databases ( n = 9), reference tracking, hand-searching of selected journals ( n = 2), grey literature searching, and expert consultation ( n = 7). A conceptual framework was generated through a thematic analysis of included articles, augmented by consultation with a Lived Experience Advisory Panel. Results: In total, 8137 articles were screened. Five articles were included. Forms of impact were connectedness, understanding of recovery, reduction in stigma, validation of personal experience, affective responses, and behavioural responses. Impact was moderated by characteristics of the recipient, context, and narrative. Increases in eating disorder behaviours were identified as a harmful response specific to recipients with eating disorders. Conclusions: Mental health recovery narratives can promote recovery. Recovery narratives might be useful for clients with limited access to peers and in online interventions targeted at reducing social isolation in rural or remote locations, but support is needed for the processing of the strong emotions that can arise. Caution is needed for use with specific clinical populations. Protocol registration: Prospero-CRD42018090923.